2021
DOI: 10.3390/plants10030504
|View full text |Cite
|
Sign up to set email alerts
|

Small Non-Coding RNAs at the Crossroads of Regulatory Pathways Controlling Somatic Embryogenesis in Seed Plants

Abstract: Small non-coding RNAs (sncRNAs) are molecules with important regulatory functions during development and environmental responses across all groups of terrestrial plants. In seed plants, the development of a mature embryo from the zygote follows a synchronized cell division sequence, and growth and differentiation events regulated by highly regulated gene expression. However, given the distinct features of the initial stages of embryogenesis in gymnosperms and angiosperms, it is relevant to investigate to what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 116 publications
(184 reference statements)
1
2
0
Order By: Relevance
“…Further, it is reported that miRNAs (e.g., miR156, miR159, miR162, miR164, miR166, miR167, miR169, miR168, miR171, miR319, miR393, and miR396) play an important role in SE [87][88][89][90][91]. Consistent with previous studies, several TFs targeted by miRNAs were recovered from the SE-related GCN.…”
Section: Discussionsupporting
confidence: 86%
“…Further, it is reported that miRNAs (e.g., miR156, miR159, miR162, miR164, miR166, miR167, miR169, miR168, miR171, miR319, miR393, and miR396) play an important role in SE [87][88][89][90][91]. Consistent with previous studies, several TFs targeted by miRNAs were recovered from the SE-related GCN.…”
Section: Discussionsupporting
confidence: 86%
“…Despite being reported as key regulators in plant SE ( Chen et al., 2018 ; López-Ruiz et al., 2019a ; Siddiqui et al., 2019 ; Alves et al., 2021 ), the ncRNAs’ involvement in plant cell plasticity is still far from being fully understood. Nevertheless, the increasing evidence of the importance of the ncRNAs-mediated regulation in cell pluripotency and regeneration ability brings to light important questions to discuss, such as: (1) To what extent do ncRNAs impact plant regeneration processes?…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miRNAs control of transcription factors and phytohormone metabolic pathways is key during different steps of the SE process (reviewed in Siddiqui et al, 2019 ). As in Arabidopsis , other angiosperms like Oryza sativa , Zea mays , Gossypium hirsutum , Solanum lycopersicum , and Dimocarpus longan , show differential expression of miRNAs at several developmental stages of SE (reviewed by Alves et al, 2021 ). In gymnosperms, on the other hand, not many miRNA studies are reported.…”
Section: Introductionmentioning
confidence: 99%